Brushed in Light Calligraphy in East Asian Cinema - Nornes, Abé Markus (University of Michigan Press, 2021)
Drawing on a millennia of calligraphy theory and history, Brushed in Light examines how the brushed word appears in films and in film cultures of Korea, Japan, Taiwan, Hong Kong, and PRC cinemas. This includes silent era intertitles, subtitles, title frames, letters, graffiti, end titles, and props. Markus Nornes also looks at the role of calligraphy in film culture at large, from gifts to correspondence to advertising. The book begins with a historical dimension, tracking how calligraphy is initially used in early cinema and how it is continually rearticulated by transforming conventions and the integration of new technologies. These chapters ask how calligraphy creates new meaning in cinema and demonstrate how calligraphy, cinematography, and acting work together in a single film. The last part of the book moves to other regions of theory. Nornes explores the cinematization of the handwritten word and explores how calligraphers understand their own work.